ASSESSMENT OF STATE JOINT LOCAL GOVERNMENT ACCOUNTS ON SERVICE DELIVERY IN IMO STATE LOCAL COUNCILS (2011-2019) - Anayo Onyeiwu, Emmanuel (African Journal of Social and Behavioural Sciences, 2024)
This paper focused on the assessment of state joint local government account (SJLGA) on service delivery in imo state local councils (2011-2019) as the focal point. The study was carried out to identify the extent to which state joint local government accounts have hindered effective service delivery. On the basis of the above, the study utilized structural functional theory as the framework of analysis. Moreover, a survey research design was used, and a questionnaire served as the primary instrument for data collection. The study population included 755 people (including political executives and bureaucrats) in Owerri Municipal, Mbaitoli, Isiala Mbano, Onuimo, Oru East, and Njaaba Local Government Areas (two local governments from each of the three zones in Imo State). The sample size was determined via the Taro Yammane formula; hence, the sample size was 262. Moreover, a simple random sampling technique was used for the study. The instrument was subjected to face and content validity and adheres to the instructions of the supervisors. The data collected were analysed via simple percentages. In line with the hypotheses, it was revealed that state joint local government accounts, significantly influence rural security, primary health care, rural road maintenance, and primary education. On the basis of these findings, the National Assembly should consider, among other things, the urgent review of the provision of the state joint local government accounts in the 1999 constitution to allow for more fiscal autonomy for local councils and to enable them to be financially independent so that they can carry out their constitutional roles and act as instruments for rural transformation.